Supramolecular interactions of carbon nanotubes with biosourced polyurethanes from 2-(2, 5-dimethyl-1H-pyrrol-1-yl)-1, 3-propanediol. (20th April 2015) - Galimberti, Maurizio; Barbera, Vincenzina; Citterio, Attilio; Sebastiano, Roberto; Truscello, Ada; Valerio, Antonio Marco; Conzatti, Lucia; Mendichi, Raniero
Abstract: Biosourced polyurethanes (PU) were synthesized from a serinol derivative containing a pyrrole ring, 2-(2, 5-dimethyl-1 H -pyrrol-1-yl)-1, 3-propanediol (SP), and stable supramolecular interaction with multiwalled carbon nanotubes (MWCNT) was established. Synthesis of SP was solvent free and with high atom efficiency: serinol was reacted with 2, 5-hexandione, obtaining the tricyclic compound 4a, 6a-dimethyl-hexahydro-1, 4-dioxa-6b-azacyclopenta[ cd ]pentalene, whose aromatization led to SP. Solvent free polymerization of SP and 1, 6-hexamethylene diisocyanate led to PU oligomers. High resolution transmission electron microscopy of CNT adducts with PU oligomers revealed individual CNT, with intact skeleton and PU oligomers tightly adhered to their surface. Suspensions of MWCNT-PU adducts in acetone were stable even after centrifugation. These results pave the way to composite material containing carbon nanofillers tightly bound to the polymer matrix, reducing their dispersion in the environment. Graphical abstract: Highlights: Serinol derivative with a pyrrole ring was prepared through Paal–Knorr reaction. Polyurethanes were synthesized from a serinol derivative containing a pyrrole ring. Synthesis of serinol derivatives were with high atomic efficiency and solvent free. Stable supramolecular interactions established between CNT and PU with pyrrole ring.